Meech Lake : The Inside Story - Monahan, Patrick (Book collections on Project MUSE., 1991)
From behind the close doors of Meech Lake comes this insider's account of the negotiations that put Canada's future on the line. Patrick J. Monahan was there throughout the negotiations and tells a compelling story of deals and dealmakers, compromise and confrontation.